2009
DOI: 10.1038/ng.385
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies identify loci associated with age at menarche and age at natural menopause

Abstract: Age at menarche and age at natural menopause are associated with causes of substantial morbidity and mortality such as breast cancer and cardiovascular disease. Studies have suggested both traits might be partially under genetic control. We performed a joint analysis of two genome-wide association studies of these two traits in a total of 17,438 women from the Nurses’ Health Study (NHS, N=2,287) and the Women’s Genome Health Study (WGHS, N=15,151). For age at menarche, we identified 10 associated SNPs (P=1×10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
301
4
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(329 citation statements)
references
References 29 publications
18
301
4
6
Order By: Relevance
“…While one initial study reported an association with the SPOCK locus that has not been replicated (77), four independent papers published in May 2009 identified an association of the age at menarche (AAM) with variability at 6q21, in or near the Lin28B gene (78,79,80,81). The robustness of this finding is reinforced by its recent confirmation in an extensive meta-analysis (82), and the fact that Lin28B had also been linked to breast development and adult height.…”
Section: Role Of Nesfatin-1 In Puberty Onset: Supporting Evidencementioning
confidence: 64%
“…While one initial study reported an association with the SPOCK locus that has not been replicated (77), four independent papers published in May 2009 identified an association of the age at menarche (AAM) with variability at 6q21, in or near the Lin28B gene (78,79,80,81). The robustness of this finding is reinforced by its recent confirmation in an extensive meta-analysis (82), and the fact that Lin28B had also been linked to breast development and adult height.…”
Section: Role Of Nesfatin-1 In Puberty Onset: Supporting Evidencementioning
confidence: 64%
“…This approach is limited for a complex phenotype because it implicates only very few genes. Previous studies used this approach to report associations of the genes CCR3, SPOCK1, LIN28B, ZNF462, TMEM38B, FKTN, FSD1L, and TAL2 with age of puberty in women (11)(12)(13)(14)(15). If we applied only this approach to our data, further research would consider one candidate gene, NMDAR2B, which was strongly associated (P < 0.000015) with AGECL.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies focused on the age at menarche, [96][97][98] one GWAS studied the age at natural menopause, 99 and the other GWAS investigated both the traits. 100 Several loci were identified for menarche, but all the four studies definitely found an association in the 6p21 locus that contained LIN28B (a height-related gene) and two GWAS detected another locus 9q31.2. In addition, two convincing loci were also identified for menopause, 19q13.42 (BRSK1) and 20p12.3 (MCM8).…”
Section: The Recent 2 Years: 2008 and 2009mentioning
confidence: 99%